Türk ceza hukukunda terörizmin finansmanının önlenmesi - Topuz, Hatice Fulya (My University, 2022)
Tez, terörizmin finansmanının Türk ceza hukuku kapsamında uluslararası anlaşmalar, kanun, tüzük, yönetmelik ve genel tebliğler uyarınca önlenmesi adına nasıl önlemlerin alındığının açıklanması, söz konusu alanda tanımlı terörizmin finansmanı suçunun soruşturma ve kovuşturulma süreçlerinin anlatılmasından ibarettir. Tezin konusunu terörizmin finansmanının önlenmesinin Türk ceza hukuku kapsamında incelenmesi oluşturmaktadır. Söz konusu tez; terör örgütleriyle çevrili ülkemiz hukukunda terörün en önemli kaynaklarından biri olan terörün ekonomik kaynağının incelenmesi, bu hususta alınan hukuki tedbirler ile cezaların incelenmesi yoluyla hukuk literatürüne katkı sağlayacaktır. Ancak tezin en önemli amacı terörizmin finansmanı suçunun yapısal unsurlarının, soruşturma ve kovuşturma usullerinin incelenerek bu kapsamda varlığını sürdüren hukuki sorunlara çözüm önerileri sunmaktır. Terörün finansmanının önlenmesi, terör örgütüne üyelik ve terör örgütüne yardım suçlarından farklı olarak ele alınmış ve 3713 sayılı Terörle Mücadele Kanunu’nun 8. maddesi yürürlükten kaldırılarak; 07/ 02/ 2013 tarihli, 6415 sayılı kanun kabul edilmiş ve söz konusu alanda çok daha spesifik uygulamalara gidilmeye çalışılmıştır. 31/ 05/ 2013 tarihli Terörizmin Finansmanının Önlenmesi Hakkında Kanunun Uygulanmasına İlişkin Usul ve Esaslar Hakkında Yönetmelik yürürlüğe girerek kanunun uygulanmasına ilişkin usul ve esaslar belirtilmeye çalışılmıştır. İşbu kanun ve yönetmelik ile, diğer mevzuat hükümlerinin yollamaları ve ayrıca konuyla ilgili uluslararası anlaşmalar söz konusu tezin temel kaynaklarını oluşturmaktadır. Tez konusunun araştırılması ve incelenmesi sırasında; konuyla ilgili mevzuat hükümleri ile sınırlı olmamak üzere Yargıtay içtihatları da incelenerek; mevzuat ve uygulama arasındaki çelişkiler tanımlanmış ve söz konusu çelişkilerin giderilmesi ve terörün finansmanının önlenmesine ilişkin olarak çözüm önerileri getirilmeye çalışılmıştır.

The purpose of the thesis; Explaining how the measures have been taken to prevent financing of terrorism under international agreements, laws, regulations and general communiques within the scope of Turkish Criminal Law consists of explaining the investigation and prosecution processes of the crime defined in the field. This thesis examines combating the financing of terrorism within the scope of Turkish Law. The thesis in question; in the law of our country surrounded by terrorist organizations; Examining the economic source of terrorism, which is one of the most important sources of terrorism, and examining the legal measures and penalties taken in this regard will contribute to the legal literature. Prevention of financing of terrorism has been handled differently from the crimes of membership and assistance to a terrorist organization and by repealing the 8th article of the Anti-Terror Law numbered 3713, In this regard, by adopting the Law No. 6415 dated 07/ 02/ 2013, much more specific applications have been attempted in this field. The Regulation on the Procedures and Principles Regarding the Implementation of the Law on the Prevention of the Financing of Terrorism dated 31/ 05/ 2013 entered into force and the procedures and principles regarding the implementation of the law were trying to be specified. This law and regulation, other legislative provisions, and also international agreements on the subject constitute the main sources of the thesis in question. During the research and examination of the thesis subject; research will be conducted, including but not limited to the provisions of the relevant legislation. Besides, by examining the case-law of the Supreme Court; Conflicts between legislation and implementation be tried to be identified. We try to find solutions to eliminate these contradictions and prevent the financing of terrorism. For the research of the thesis, the texts of the law, especially the Law on the Prevention of Terrorism Law and the Prevention of the Financing of Terrorism, the International Convention on the Prevention of the Financing of Terrorism, published articles and theses, books, publications, communiqués, and regulations will be used as sources. Also, practical applications will be examined with the decisions of the Supreme Court, Regional Court of Justice, and the Constitutional Court.
Keywords: Ceza hukuku; Combating Terrorism; Criminal law; Economic Crime; Ekonomik Suç; Financing; Finansman; Prevention of Terrorist Financing; Terör; Terör Finansmanının Önlenmesi Terrorism; Terörle Mücadele; Turkey; Türkiye